Effect of Chaetomium globosum Inoculation and Organic Matter n Phosphorus Mobilization in Soil and Yield of Clusterbean - Yadav, B K; Niwas, Ram; Yadva, R S; Tarafdar, J C (Annals of Arid Zone, 2016)
Greenhouse experiment was conducted to study the effect of organicitt(eOrM) and Chaetomium globosum on enzyme activities, nutrient uptake and yield of usterbean. The OM gradient (1% and 3%) was created by application of vermicompost a sandy soil. In general 1.7% more decline in pH and 18% more increase in EC was observed due to inoculation of C. globosum in presence of OM. As compared to control soil, the e~ancement of acid phosphatase activity was observed up to 35% with OM alone and 50% when OM was combined with C. globosum. The increase in alkaline phosphatase activi was 12% more due to inoculation of C. globosum in OM compared to application of only OÂ¥. Increase in phytase activity was 71% more in OM treatment with C. globosum, which was t5% higher ~han applic~tion of OM alo~e. In general 6%, 23% and 10% more N, P and K a~cumulated in plant WIth C. globosum in presence of OM as compared to no inoculationl The seed ~~~ of clusterbean increased by 7.4% with C. globosum in the presence of hil~h level of Key words: Organic manure, Chaetomium globosum, acid and alkaline phosphata e, phytase, nutrient content, clusterbean.